Challenges faced by parents raising adolescents abusing substances : parents’ voices - Mathibela, Faith; Skhosanna, Rebecca (Social Work/Maatskaplike Werk, 2019)
Substance abuse among adolescents continues to be a serious condition that affects their growth, learning and relationships with their parents. This article discusses the effects of substance abuse on parents who are raising adolescents abusing substances. It is based on a study that sought an in-depth understanding of the experiences, challenges and coping strategies of parents raising adolescents abusing substances in the community of Ramotse in Hammanskraal, Gauteng. A qualitative research approach with purposive and snowball sampling was abused. Data were collected through semi-structured interviews and analysed abusing Tesch’s eight steps. Guba’s model was applied for data verification. The findings reflect the challenges that parents face and the article offers suggestions for social work policy and practice to deal with substance abuse. Ethical issues were also taken into consideration.